2023
DOI: 10.1038/s41536-023-00301-7
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral organoids transplantation repairs infarcted cortex and restores impaired function after stroke

Abstract: Stroke usually causes prolonged or lifelong disability, owing to the permanent loss of infarcted tissue. Although a variety of stem cell transplantation has been explored to improve neuronal defect behavior by enhancing neuroplasticity, it remains unknown whether the infarcted tissue can be reconstructed. We here cultured human cerebral organoids derived from human pluripotent stem cells (hPSCs) and transplanted them into the junction of the infarct core and the peri-infarct zone of NOD-SCID mice subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“… 132 A recent notable advancement has been made by scientists who successfully transplanted brain tissue organoids derived from human cells into mice suffering from stroke. 133 This transplantation procedure effectively restored impaired tissue and reinstated motor functions. 134 , 135 Furthermore, upon transplantation into the visual cortex of rat brains, the brain organoids exhibited seamless integration into the host tissue, exhibiting progressive development of blood vessels, enlargement in size, generation of neuronal projections, and establishment of synaptic connections.…”
Section: Future Strategies For Treating Neurological Diseasesmentioning
confidence: 93%
See 2 more Smart Citations
“… 132 A recent notable advancement has been made by scientists who successfully transplanted brain tissue organoids derived from human cells into mice suffering from stroke. 133 This transplantation procedure effectively restored impaired tissue and reinstated motor functions. 134 , 135 Furthermore, upon transplantation into the visual cortex of rat brains, the brain organoids exhibited seamless integration into the host tissue, exhibiting progressive development of blood vessels, enlargement in size, generation of neuronal projections, and establishment of synaptic connections.…”
Section: Future Strategies For Treating Neurological Diseasesmentioning
confidence: 93%
“… 133 This transplantation procedure effectively restored impaired tissue and reinstated motor functions. 134 , 135 Furthermore, upon transplantation into the visual cortex of rat brains, the brain organoids exhibited seamless integration into the host tissue, exhibiting progressive development of blood vessels, enlargement in size, generation of neuronal projections, and establishment of synaptic connections. 136 , 137 Moreover, the introduction of human brain organoids into the brains of neonatal rats, specifically those aged 2–3 days, a critical period characterized by ongoing neural connectivity development, resulted in the subsequent growth and occupation of approximately one‐third of the rat brain hemisphere by these transplanted human brain organoids.…”
Section: Future Strategies For Treating Neurological Diseasesmentioning
confidence: 93%
See 1 more Smart Citation
“…Cao et al. [ 178 ] used cylinder, grid walking, and deglutition tests to assess the recovery of sensory and motor functions in stroke mice transplanted with human brain organoids and showed that neuronal activity of transplanted organoids was critical for the recovery of sensory-motor functions after stroke.…”
Section: Engineering Organoids With Applications In Tissue Repair And...mentioning
confidence: 99%
“…Furthermore, using a small molecule cocktail named CEPT (chroman 1, emricasan, polyamines, trans-ISRIB), a polypharmacological approach can enhance cytoprotection and improve organoid survival (Ryu et al, 2023 ). In addition, organoid transplantation was confirmed to alleviate the cellular stress in organoids (Bhaduri et al, 2020 ) and improve organoid maturity, cellular complexity, and brain function (Cao et al, 2023 ; Jgamadze et al, 2023 ; Wang et al, 2023 ). Lastly, Vertesy et al ( 2022 ) developed a computational algorithm method, Gruffi, to remove the stressed cells from the organoid single-cell RNAseq dataset, and therefore, improves the bioinformatic data analysis after the organoids are collected.…”
Section: Generation Of Brain Organoidsmentioning
confidence: 99%